Answer:
Part a)
![v = \sqrt{xg + (MLg)/(m)}](https://img.qammunity.org/2020/formulas/physics/college/212mcgx1uvthfv0o1bcvbex3bpqn6wnnss.png)
Part b)
t = 12 s
Step-by-step explanation:
Part a)
Tension in the rope at a distance x from the lower end is given as
![T = (m)/(L)xg + Mg](https://img.qammunity.org/2020/formulas/physics/college/fru3xtsju4plywnw62x5xlcjnhpep5sw5c.png)
so the speed of the wave at that position is given as
![v = \sqrt{(T)/(\mu)}](https://img.qammunity.org/2020/formulas/physics/high-school/9lff6q72slumjkyw4eqn0w6r1xtga10zuj.png)
here we know that
![\mu = (m)/(L)](https://img.qammunity.org/2020/formulas/physics/college/g267uimdv1bkk2mdcxgunooircdmnd0i64.png)
now we have
![v = \sqrt{( (m)/(L)xg + Mg)/(m/L)](https://img.qammunity.org/2020/formulas/physics/college/2eqlu0wd7od5k9hc1hsm89xpowzfx5hs76.png)
![v = \sqrt{xg + (MLg)/(m)}](https://img.qammunity.org/2020/formulas/physics/college/212mcgx1uvthfv0o1bcvbex3bpqn6wnnss.png)
Part b)
time taken by the wave to reach the top is given as
![t = \int \frac{dx}{\sqrt{xg + (MLg)/(m)}}](https://img.qammunity.org/2020/formulas/physics/college/m9rcj8nu50foq02e5eheq3cm1vpnx020lm.png)
![t = (1)/(g)(2\sqrt{xg + (MLg)/(m)})](https://img.qammunity.org/2020/formulas/physics/college/z1lzorbrckz1kzo8vgacw71dbz8k1qpyng.png)
![t = (2)/(9.8)(\sqrt{(39.2* 9.8) + (8(39.2)(9.8))/(1)})](https://img.qammunity.org/2020/formulas/physics/college/hg2cfob8ahwu10fobiilb8jmojeavyk7qg.png)
![t = 12 s](https://img.qammunity.org/2020/formulas/physics/high-school/aik1xd3hyvu8fds32thfwsh42976c8k6ey.png)